Association between handgrip strength and bone mineral density of Brazilian children and adolescents stratified by sex: a cross-sectional study - Saraiva, Bruna Thamyres Ciccotti [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Freitas Júnior, Ismael Forte [UNESP]; de Sousa, Daniel Eduardo Rodrigues [UNESP]; Gobbo, Luis Alberto [UNESP]; Tebar, William Rodrigues [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (Springer Nature, 2021)
Background: To examine the association of handgrip strength (HGS) and bone mineral density (BMD) of Brazilian children and adolescents. Methods: The sample included 243 children and adolescents aged from 4 to 15 years (9.3 ± 2.2 years), 171 males and 72 females. The following measurements were performed: weight, height, trunk length, and years to the peak height velocity (PHV). The percentage lean soft tissue (PLST), percentage fat mass (PFM), and BMD were obtained using Dual Energy X-ray Absorptiometry (DXA) and HGS using a dynamometer. Results: In girls, HGS was positively associated with higher BMD, even after the adjustments, by arms [β = 0.006; p < 0.001], legs [β = 0.014; p < 0.001], pelvis [β = 0.019; p < 0.001], trunk [β = 0.013; p < 0.001], spine [β = 0.013; p = 0.008], and total body [β = 0.009; p < 0.001]. The same occurred in the boys, even after the adjustments a positive relationship was observed, whereas higher HGS was related to greater BMD in arms [β = 0.006; p < 0.001], legs [β = 0.017; p < 0.001], pelvis [β = 0.014; p < 0.001], trunk [β = 0.009; p < 0.001], spine [β = 0.008; p < 0.001], and total body [β = 0.007; p < 0.001]. Conclusion: HGS was positively associated to BMD in boys and girls, regardless of age, PHV, PLST, and PFM.
Keywords: Adolescent; Bone density; Child; Health; Strength